Interpretative modeling of impurity transport and tungsten sources in WEST boundary plasma. (22nd October 2021) - Ciraolo, G.; Di Genova, S.; Yang, H.; Gallo, A.; Fedorczak, N.; Bufferand, H.; Gunn, J.P.; Tamain, P.; Guirlet, R.; Guillemaut, C.; Desgranges, C.; Bourdelle, C.; et al.
Abstract: Contamination of core plasma by high-Z impurities, especially tungsten (W), is the main reason for the very high level of radiated power in WEST experiments. Intrinsic light impurities, mainly oxygen and carbon, play a dominant role in the sputtering of W on plasma facing components. In this contribution, we present a detailed analysis of WEST experiments supported by numerical modeling performed with the transport code SOLEDGE-EIRENE providing a clear picture of light impurities transport and poloidal distribution. Moreover, making use of SOLEDGE-ERO2.0 simulations, possible strategies to reduce core contamination due to W penetration are presented.